Pengaruh Social Support terhadap Resiliensi Emosional pada Siswa SMP Negeri 26 Surabaya - Akbar, Nazwa Aulia; Aulia, Naya Fitrah; Kusnanda, Raniah Ratna Brillianti; Halida, Arfin Nurma (LPPM Universitas Informatika dan Bisnis Indonesia, 2024)
The main issue raised was the importance of social support in helping teenagers face emotional challenges. The aim of this research is to analyze the effect of social support on emotional resilience in students at SMPN 26 Surabaya. This research uses quantitative methods with a population of 8th grade students at SMP Negeri 26 Surabaya of 346 students and a sample of 172 students using the Isaac and Michael table with an error rate of 5%. The data analysis technique uses regression analysis to measure the significance of the relationship between variables. The research results show that social support has a significant influence on students' emotional resilience, with a significance value of 0.009, which indicates a positive relationship. These findings emphasize the need for community-based interventions to increase social support in school and family settings. Keywords: Social Support, Emotional Resilience.